Eliciamento Cognitivo: A Propaganda Persuasiva nas Revistas Semanais Impressas - Whitaker, Múcio (2006)
This work is focused to the use of - by the advertising development agencies different syntax in the marketing communication field and intend to identify the persuasive purposes applied thru many forms of advertising, by the analysis of some advertisements published in the print media weekly magazines and some direct sales catalogs. The manipulative purpose through persuasive messages, using different syntax, is the target to brand recognition, sales increase and to provide cognition elicity, by the consumption stimulus. The persuasive advertisements are in charge for the use of the sensory system as new organoleptical syntax. This way, it was researched recent and classical bibliography on wide themes as advertising, publicity, merchandising and persuasion in order to identify and to prove the presence of different persuasive syntax this work shows some examples of persuasive advertisements which may validate and establish these theory. The main reference of inspiration was the book published by Al Ries and Jack Trout.